MEMPERJUANGKAN AKSES PENDIDIKAN MELAMPAUI BATAS GEOGRAFIS DI FLORES TIMUR: TRANSISI DARI DESA KE SEKOLAH - Yanuarius Payong Gega; Nurul Fitriana; Elza Jelita; Ega Santika; Azril Sapitra (ENTINAS: Jurnal Pendidikan dan Teknologi Pembelajaran, 2024)
Education is considered an inherent human right essential to the realization of sustainable development. However, certain remote areas, such as in remote areas of East Flores, struggle with limited access to quality education due to lacking educational infrastructure and challenging topographic terrain. The main objective of this investigation is to investigate initiatives formulated to overcome obstacles posed by lack of infrastructure and geographical barriers, thereby raising educational standards in remote corners of East Flores. Using qualitative methodology, the research carried out data collection through on-site observations, comprehensive dialogue with relevant stakeholders, and thorough scrutiny of existing literature. These findings highlight a variety of efforts, including the creation and improvement of educational facilities such as schools, libraries, and additional support structures; increasing the quality and quantity of educators through training schemes and incentive initiatives; exploitation of information and communication technology to transcend spatial barriers; cooperative efforts with national authorities, local administrations, and non-governmental entities to offer alternative education schemes; and fortification of community involvement and participation in the realm of education. This study lends credence to the formulation of adaptive educational tactics and regulations that are attuned to the particularities of the geographic landscape and infrastructure deficiencies in remote environments. Additionally, it explains the importance of multifaceted and collaborative methodologies in efforts aimed at improving the accessibility and quality of education in distance settings.